3-(3-Azabicyclo[2, 2, 1]heptan-2-yl)-1,2,4-oxadiazoles as Novel Potent DPP-4 Inhibitors to Treat T2DM - Tatiana V. Zinevich; Ivan O. Maslov; Olga G. Kirichenko; Sergey V. Shorshnev; Maxim A. Gureev; Fedor M. Dolgushin; Yuri B. Porozov; Vladimir M. Trukhan (Pharmaceuticals)
Background: Type 2 diabetes mellitus (T2DM) is a prevalent metabolic disease with global implications, necessitating effective management strategies. Dipeptidyl peptidase IV (DPP-4) inhibitors have shown promise as potent agents for T2DM treatment. Methods: This study combines chemical synthesis, molecular modelling, and inhibitory activity assays to characterise the structure–activity relationship of novel isomeric 1,2,4-oxadiazole-substituted derivatives of the 2-azabicyclo[2.2.1]heptane scaffold acylated with (R)-3-amino-4-(2,4,5-trifluorophenyl)butanoic acid. Results: In this article, we demonstrate the efficacy of new compounds as robust inhibitors of DPP-4. The attempts to further modify neogliptin (our lead compound described previously) resulted in a more potent DPP-4 inhibitor 9a (IC50 = 4.3 nM), which did not mediate any substantial inhibition of DPP-8 and DPP-9. Conclusions: This study demonstrates that pseudo peptides incorporating (R)-3-amino-4-(2,4,5-trifluorophenyl)butanoic acid, a 2-aza-bicyclo[2.2.1]heptane moiety, and 1,2,4-oxadiazole substituents act as potent and selective DPP-4 inhibitors. By the stereochemical refinement of oxadiazole derivatives of neogliptin, we discovered compound 9a, a strong candidate for further development in T2DM treatment.